AI Comments: Leveraging the Global Knowledge Corpus, One Way or Another - Tingey, Kenneth B. (Journal of Knowledge Management Practice, 2025)
Submitted to the White House and to the National Telecommunications and Information Administration of the United States Department of Commerce on May 11, 2023 and updated on June 5, 2023 in response to their April 13, 2023 Request for Comments, this paper makes the case for AI as a secondary tool in knowledge management. More central to the question is the need to provide tools for scientists and other knowledge workers to compose and direct the actions of computers and digital networks in their professional and organizational roles and make scientific and administrative processes available for use in integrative and reflective ways. As to AI safety, only when valid and reliable answers are known can AI outcomes be validated. Qualitative and quantitative methodologies, including peer review, are solely capable of being carried out by humans using their wide array of senses and abilities. Once organized and validated in these ways, computers, including AI, can instantly and readily derive contexts and support high-level classification and calculation to apply them at scale.
Keywords: knowledge management; artificial intelligence; AI